Analisis pendapatan usaha industri kerupuk amplang di Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat - Salman Alfarisyi; Siti Hodijah; Nurhayani Nurhayani (e-Journal Perdagangan Industri dan Moneter, 2019)
This study aims to analyze the socio-economic characteristics of entrepreneurs and the amplang cracker industry business, the magnitude of the amplang cracker industry business income, and the factors that affect the income of the amplang cracker industry entrepreneur in Tungkal Ilir District, Tanjung Jabung Barat Regency. The research method used in this study is a survey method, with descriptive analysis and quantitative analysis. Based on the results of data processing using the OLS method in multiple linear regression equations, the results obtained are: The socio-economic characteristics of all amplang cracker industry entrepreneurs are 83.33 percent with a high school graduate/equivalent. The average number of dependents and the number of workers is 4 people. The average net income of Rp. 15,753,334,- per month. Simultaneously, the variables of production costs, the amount of production, and the workforce have a significant effect on the business income of the amplang cracker industry. Partially shows that production costs, and the amount of production have a positive and significant effect on the business income of amplang crackers. Meanwhile, labor has no significant effect on the business income of the amplang cracker industry. Keywords: Production, Labor, Revenue of amplang crackers industry